2017
DOI: 10.3390/s17050967
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Directional Drilling-Length Detection Technology While Drilling Based on Bi-Electro-Magnetic Sensing

Abstract: The drilling length is an important parameter in the process of horizontal directional drilling (HDD) exploration and recovery, but there has been a lack of accurate, automatically obtained statistics regarding this parameter. Herein, a technique for real-time HDD length detection and a management system based on the electromagnetic detection method with a microprocessor and two magnetoresistive sensors employing the software LabVIEW are proposed. The basic principle is to detect the change in the magnetic-fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…MR sensors have been used in commercial applications operating at temperatures up to 225 °C, pressures up to 20,000 psi and mechanical shocks up to 1500 g [ 132 ]. Recent research has also shown that MR sensors can be used to calculate the length of directional wells, where the length can be used in fitting the drilling profile, computing the deviation, designing the drilling profile, and developing an algorithm for automated directional drilling [ 133 ], to measure NMR signals at room temperature [ 134 ] and operate at temperatures up to 175 °C for 5000 h with low energy consumption [ 128 ]. Apart from meeting the criteria for use in harsh environments low power consumption is a key advantage in these sensors since power is at a premium in downhole environments.…”
Section: Discussion: Research Opportunities For Other Types Of Magmentioning
confidence: 99%
“…MR sensors have been used in commercial applications operating at temperatures up to 225 °C, pressures up to 20,000 psi and mechanical shocks up to 1500 g [ 132 ]. Recent research has also shown that MR sensors can be used to calculate the length of directional wells, where the length can be used in fitting the drilling profile, computing the deviation, designing the drilling profile, and developing an algorithm for automated directional drilling [ 133 ], to measure NMR signals at room temperature [ 134 ] and operate at temperatures up to 175 °C for 5000 h with low energy consumption [ 128 ]. Apart from meeting the criteria for use in harsh environments low power consumption is a key advantage in these sensors since power is at a premium in downhole environments.…”
Section: Discussion: Research Opportunities For Other Types Of Magmentioning
confidence: 99%
“…Moreover, FGIL provides following advantages in contrast to the conventional rigid GIL: Acceleration dampers are not required; there is no need for corrosion protection; the incorporation of structural flexibility; a substantially reduced bending radius and lay length, as well as lesser required land area at bends. Moreover, studies [38][39][40] mentioned that flexible enclosures and cables, like FGIL, are feasible for horizontal directional drilling (HDD) based subsurface laying technique which eliminates the trench requirement and is advantageous regarding cable and pipe laying in urban localities. FGIL is basically comprised of a flexible-stranded-conductor, flexible-thermoplasticenclosure, open cell foam of significant structural strength for concentric conductor alignment and a compressed mixture of dielectric gases as the primary insulation medium.…”
Section: Introductionmentioning
confidence: 99%